Quality Characteristics of Spent Duck Sausages Containing Surimi Like Material Substitution During Refrigerated Storage - Ismail, I.; Huda , N.; Ariffin, F. (International Journal of Poultry Science, 2014)
The quality characteristics of duck sausages prepared using different treatment were evaluated. Physicochemical, sensory and microbial properties of sausages containing duck surimi-like material substitution with cryoprotectant added (CPP) and without cryoprotectant added (NPP), antioxidant added (BHA) and, duck mince (as the control, CON) were compared. CPP and NPP sample had significantly higher (p<0.05) moisture content and lower protein and fat content compared with CON sample. The thiobarbituric acid-reactive substances (TBARS) value of all sample increased as the storage time increased up to day 30, but thereafter it decreased in all of the samples. CPP sample had significantly lower TBARS value (p<0.05) and this value remained lower than those of the other samples throughout the refrigerated storage time. Addition of duck surimi-like material to the sausages had significant effects (p<0.05) on hardness, gumminess and chewiness values of CPP and NPP sample. Treatment had no significant effect on sensory attributes of sausages prepared from duck meat. CPP sample had lower microbial activity during 40 days of refrigerated storage. However, BHA sample had no significant difference in microbial activity compared with CON sample. The results indicate that duck surimi-like material substitution with cryoprotectant added improves quality characteristics of duck sausages during refrigerated storage than the other treatments.